Innovative design of bicycle helmet liners. (October 2014) - Teng, Tso-Liang; Liang, Cho-Chung; Nguyen, Van-Hai
Bicycle helmets are designed to reduce the acceleration/deceleration of the head during impacts. During an accident, the main parts of a helmet responsible for shock absorption are the energy-absorbing liner and the outer shell. In the present study, several geometrical structures of convex acrylonitrile butadiene styrene plastic shell, such as a truncated conical form and a semi-spherical form, were investigated for their energy-absorbing capacity. Moreover, several liner dimension parameters were also optimised. The energy was absorbed in these structures by a combination of folding and collapsing. The idea of a sandwich liner using the aforementioned structures was also constructed to analyse its advantages compared to their single structures. This study performs finite element analyses on helmet impact tests using LS-DYNA software based on the EN1078 standards. The purpose of the present study was to determine a structure of liner that reaches high effective protection and to design helmet models with single and dual liners. The final work in this study was performed to optimise the height cone of linear semi-sphere cones. This innovative design for a helmet liner demonstrated high energy-absorbing capabilities. Moreover, this helmet impact test model can serve as a valuable tool to assist future development of safety-helmet technologies.